A 5-Year Review of Invasive Fungal Infection at an Academic Medical Center - Li, Yaling; Gao, Yali; Niu, Xueli; Wu, Yutong; Du, Yimei; Yang, Ying; Qi, Ruiqun; Chen, Hongduo; Gao, Xinghua; Song, Bing; Guan, Xiuhao (Frontiers in Cellular and Infection Microbiology, 2020)
Background: Invasive fungal infection (IFI) is one of the most common nosocomial infections. However, data on the epidemiology of IFI and susceptibility to antifungal agents in China are quite limited, and in particular, no current data exist on the microbiological and clinical characteristics of IFI patients in Northeast China. Objectives: The purpose of this study was to provide a retrospective review of the clinical characteristics, laboratory test results and risk factor predictions of inpatients diagnosed with IFI. Multivariate regression analysis was used to assess prognostic factors associated with the mortality of these patients. Methods: We retrospectively analysed the results from 509 patients with IFI extracted from the First Hospital of China Medical University from January 2013 to January 2018. Results: Neutrophil numbers, total bilirubin, length of stay in the ICU, renal failure, use of immunosuppressants within the past 30 days, stomach tube placement and septic shock were risk factors for death from IFI. Recent surgery (within 2 weeks) and drainage tube placement did not increase mortality in these IFI patients. Increased serum levels of PCT (AUC 0.601, 95% CI 0.536-0.665, P=0.003) and CRP (AUC 0.578, 95% CI 0.512-0.644, P=0.020) provided effective predictors of 30-day mortality rates. Conclusions: We report for the first time epidemiological data on invasive fungal infections in Northeast China over the past five years. Despite the limited available clinical data, these findings will greatly aid clinical health care workers with regard to the identification, prevention and treatment of IFI in hospitalized patients.